Dental/ Medical Practice and Right to Information Act: Current Status (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
The quest for information is one of the basic instincts in any civilised society. Secrecy is mostly doubted and apprehensions are raised that something wrong is being done, if it is not open. Attempts are being made worldwide to enact laws for bringing transparency in the functioning of the government. The first attempt to allow free access to information held in government custody in India came in the form of the Freedom of Information Act in 2002, while Right to Information (RTI) Act 2005 1is a further refinement of this Act. In India, large proportion of health care services involving both dental and medical services are being provided in the public sector. Accordingly, as per the provisions of the RTI Act, they are under the ambit of RTI Act. Thus, the information existing in these public offices can be asked by any citizen of this country without specifying any reason. While providing information related to a patient, on one side there is issue of openness that comes up following the law of the land, while on other side there are apprehensions regarding the breach of trust that exists between the doctor and patient governed by code of dental/ medical ethics. What are the provisions in law and the available court judgments related on this aspect? The paper attempts to highlight this important aspect of dental/ medical profession in light of the law and related judgments.
Keywords: Right to Information; Dental Profession; Medical Profession; Judgements